The influence of bioavailable heavy metals and microbial parameters of soil on the metal accumulation in rice grain. (October 2017) - Xiao, Ling; Guan, Dongsheng; Peart, M.R.; Chen, Yujuan; Li, Qiqi; Dai, Jun
Abstract: A field-based study was undertaken to analyze the effects of soil bioavailable heavy metals determined by a sequential extraction procedure, and soil microbial parameters on the heavy metal accumulation in rice grain. The results showed that Cd, Cr, Cu, Ni, Pb and Zn concentrations in rice grain decreases by 65.9%, 78.9%, 32.6%, 80.5%, 61.0% and 15.7%, respectively in the sites 3 (far-away), compared with those in sites 1 (close-to). Redundancy analysis (RDA) indicated that soil catalase activity, the MBC/MBN ratio, along with bioavailable Cd, Cr and Ni could explain 68.9% of the total eigenvalue, indicating that these parameters have a great impact on the heavy metal accumulation in rice grain. The soil bioavailable heavy metals have a dominant impact on their accumulation in rice grain, with a variance contribution of 60.1%, while the MBC/MBN has a regulatory effect, with a variance contribution of 4.1%. Stepwise regression analysis showed that the MBC/MBN, urease and catalase activities are the key microbial parameters that affect the heavy metal accumulation in rice by influencing the soil bioavailable heavy metals or the translocation of heavy metals in rice. RDA showed an interactive effect between Cu, Pb and Zn in rice grain and the soil bioavailable Cd, Cr and Ni. The heavy metals in rice grain, with the exception of Pb, could be predicted by their respective soil bioavailable heavy metals. The results suggested that Pb accumulation in rice grain was mainly influenced by the multi-metal interactive effects, and less affected by soil bioavailable Pb. Graphical abstract: Highlights: RDA shows that bioavailable metals and microbiology explains 68.9% of the eigenvalue. The bioavailable metals measured by BCR method are better for predicting rice metals. Soil bioavailable Cd, Cr and Ni enhance Cu and Pb, but reduce Zn in rice grain. MBC/MBN, urease and catalase activities are the key parameters affecting rice metals. Heavy metals in rice grain decreases by 15.7%–80.5% with sampling distance.